Heterogen katalysierte Hydrierung von Kohlendioxid zu Methan unter erhöhten Drücken. Issue 3 (13th December 2012) - Schoder, Melanie; Armbruster, Udo; Martin, Andreas
<x xml:space="preserve">Abstract</x> Ni‐ and Ru‐containing supported catalysts were prepared and used for the CO2 hydrogenation to methane (Sabatier reaction) in the gas phase. Tests on the effect of the reaction temperature and pressure were in the focus. ZrO2 and γ‐Al2O3 were used as suitable catalyst supports. CO2 and H2 conversions of 70 – 80 % and selectivity to methane of > 99 % were reached. TiO2 and SiO2 based catalysts exclusively lead to CO and seem to be not suited for this reaction. The investigations on the pressure effect impressively demonstrated the influence on the chemical equilibrium. CO2 and H2 can be nearly completely converted with > 99.9 % selectivity to methane over Ru/ZrO2.